PERANAN WARGA MADRASAH DALAM MEWUJUDKAN PROGRAM ADIWIYATA DI MTS AL-FALAH ARUNGKEKE KABUPATEN JENEPONTO - Kasmawati, Kasmawati (Eklektika: Jurnal Pemikiran dan Penelitian Administrasi Pendidikan, 2018)
The purpose of this paper is to find out how the role of school people and the government in the Adiwiyata program at Arungkeke MTs Al-Falah Jeneponto district. The role of the madrasa community in this case the headmaster in the Adiwiyata program namely as the originator of the main idea, policy makers who support the adiwiyata program, fostering trust able to gain achievements and role models for all madrasas have run optimally but are often constrained by funding problems. Likewise the role of subject teachers, PLH teachers and homeroom teachers in the Adiwiyata program is as the main person in charge of delivering values, skills and knowledge about environmental material and encourages students to carry out activities that reflect caring and culturally both individually or group. Other roles of the madrasa community, such as the madrasa committee, in the Adiwiyata program, which are contributing in the form of thoughts, funds and other contributions have not been maximized. TU employees, laboratory staff and librarians acted as pioneers in the management of facilities and infrastructure and the success of the Adiwiyata program administration and executing supporters had gone well.